The Influence of Physical and Mental Workload and Energy Intake on Nurse Work Fatigue in the Inpatient Room of the Dr. Pirngadi Regional General Hospital - Sarah Adinda; Gerry Silaban; Nurmaini Nurmaini (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Fatigue is a mechanism in which the body has to warn that something is disturbing the body, and it can recover after resting. Fatigue is one of the factors causing work accidents which causes as many as 2 million workers to die each year, and as many as 18,828 people (32.8%) out of 58,115 samples experience fatigue at work. The purpose of this study was to analyze the effect of physical and mental workload as well as energy intake on the work fatigue of nurses in the inpatient room of Dr. Pirngadi Regional General Hospital. This quantitative study uses a cross-sectional design using a proportional random sampling technique. The sample in this study was the nurse in the Inpatient Room at Dr. Pirngadi Regional General Hospital, namely as many as 63 nurses. Work fatigue was measured using a reaction timer, the physical workload was measured using pulse calculations, the mental workload was measured using the NASA-TLX questionnaire, and energy intake was measured using the estimated food record questionnaire. The data analysis used was univariate, bivariate with the Pearson Correlation test and multivariate with the Multiple Linear Regression test. The results of the Pearson Correlation test analysis showed that there was a significant influence between physical workload on work fatigue (p = 0.001, r = 0.424), mental workload on work fatigue (p = 0.002, r = 0.385), and energy intake on work fatigue (p = 0.0005, r = -0.477). At the same time, the results of the Multiple Linear Regression test analysis showed that the R Square value was 0.412 or 41.2%. Thus it can be concluded that 41.2% of the causes of work fatigue can be explained through the variables of physical workload, mental workload and energy intake in nurses in the Inpatient Room of Dr. Pirngadi Regional General Hospital. Keywords: Energy Intake, Fatigue, Inpatient Room